2015
DOI: 10.1007/s11154-016-9334-7
|View full text |Cite
|
Sign up to set email alerts
|

Using systematic reviews for hazard and risk assessment of endocrine disrupting chemicals

Abstract: The possibility that endocrine disrupting chemicals (EDCs) in our environment contribute to hormonally related effects and diseases observed in human and wildlife populations has caused concern among decision makers and researchers alike. EDCs challenge principles traditionally applied in chemical risk assessment and the identification and assessment of these compounds has been a much debated topic during the last decade. State of the science reports and risk assessments of potential EDCs have been criticized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 142 publications
0
19
0
Order By: Relevance
“…1314 These rebuttals of the UNEP/WHO report raised a number of issues including concerns that the report did not use systematic review criteria in the evaluation of evidence. 15 Yet, these rebuttals included many scientifically inaccurate comments, specifically misrepresenting criteria for interpreting causation as originally elaborated by Sir Austin Bradford Hill some 50 years ago, 16 incorrectly suggesting that standardised ‘weight of evidence’ approaches can be readily applied to evaluate endocrine disruption, and dismissing low-dose effects as well as non-linear and non-monotonic exposure–response relationships that are extremely well documented. Concerns raised about the UNEP/WHO report were rebutted in a number of recent articles by the UNEP/WHO authors and others.…”
Section: Edcs: How Controversial Are They?mentioning
confidence: 99%
“…1314 These rebuttals of the UNEP/WHO report raised a number of issues including concerns that the report did not use systematic review criteria in the evaluation of evidence. 15 Yet, these rebuttals included many scientifically inaccurate comments, specifically misrepresenting criteria for interpreting causation as originally elaborated by Sir Austin Bradford Hill some 50 years ago, 16 incorrectly suggesting that standardised ‘weight of evidence’ approaches can be readily applied to evaluate endocrine disruption, and dismissing low-dose effects as well as non-linear and non-monotonic exposure–response relationships that are extremely well documented. Concerns raised about the UNEP/WHO report were rebutted in a number of recent articles by the UNEP/WHO authors and others.…”
Section: Edcs: How Controversial Are They?mentioning
confidence: 99%
“…Report of proceedings from a workshop held in Weybridge, UK, 2–4 December 1996; World Health Organisation (WHO) and United Nations Environment Program (UNEP), 2012). As several epidemiological studies addressing this issue have been published over the past 10 years, a systematic evaluation of the epidemiological evidence on effects of environmental endocrine disrupting xenobiotics including quantitative meta-analyses of data, where feasible, has now become timely (Beronius and Vandenberg, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…At that time, systematic review methodology in toxicology and chemical risk assessment was less developed than it has become more recently (see e.g. [34][35][36]), and the EviEM Executive Committee concluded that validation of the review methods would require significant efforts. One of the difficulties with the suggested review question was to define the outcome.…”
Section: Framing and Prioritisation Of Review Questionsmentioning
confidence: 99%